Reproduction in Punganur cattle - BRAMHAIAH, K VEERA; RAO, S T VIROJI; REDDY, Y RAVINDRA (The Indian Journal of Animal Reproduction, 2003)
Reproductive performance over a period of 5 years of Punganur cattle was analysed. The datarevealed that the performance of Punganur cattle is as good as other dual purpose cattle and iscomparable with the other Indian breeds. The parameters recorded were age at puberty 827.86 ±48.15 days, body weight at puberty 109.00 ± 3.51 Kgs, age at first calving 1240.14 ± 89.87 days, postpartumservice period 152.00 ± 14.50 days, number of services per conception 1.57 ± 0.07, gestationperiod 284.04 ± 0.83 days and inter calving period 473.46 ± 18.13 days, respectively.
Keywords: Punganur cattle; puberty; age at first calving; calving interval